2011
DOI: 10.1126/science.1202599
|View full text |Cite
|
Sign up to set email alerts
|

Context Modularity of Human Altruism

Abstract: Whereas altruism drives the evolution of human cooperation, ethno-religious diversity has been considered to obstruct it, leading to poverty, corruption, and war. We argue that current research has failed to properly account for the institutional environment and how it affects the role diversity plays. The emergence of thriving, diverse communities throughout human history suggests that diversity does not always lead to cooperation breakdown. We conducted experiments in Mostar, Bosnia-Herzegovina with Catholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 15 publications
2
57
0
Order By: Relevance
“…Results have so far been mixed, suggesting that the precise details of the ecological context mediating altruism are important and their effect is not yet fully understood. Alexander & Christia [8] found that ethnic differences in Mostar, Bosnia can enhance co-operation in some institutional contexts but not others. In an urban context, Wilson et al [9] found that the quality of a neighbourhood (estimated from self-reported levels of support from family, school and neighbourhood) in Binghampton, U.S.A. positively predicted the number of dropped letters that were picked up and posted back.…”
Section: Introductionmentioning
confidence: 99%
“…Results have so far been mixed, suggesting that the precise details of the ecological context mediating altruism are important and their effect is not yet fully understood. Alexander & Christia [8] found that ethnic differences in Mostar, Bosnia can enhance co-operation in some institutional contexts but not others. In an urban context, Wilson et al [9] found that the quality of a neighbourhood (estimated from self-reported levels of support from family, school and neighbourhood) in Binghampton, U.S.A. positively predicted the number of dropped letters that were picked up and posted back.…”
Section: Introductionmentioning
confidence: 99%
“…Pasquale & Samii, 2013) and the resilience of fairness norms (Whitt & Wilson, 2007). At the same time, conflict experience has been linked to increased favouritism of the in-group ("parochialism") (Bauer et al, 2013), which however diminishes through frequent nonthreatening post-conflict interactions with members of other groups (Alexander & Christia, 2011).…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…pressure (study participants are asked to decide cooperate or defect within certain seconds in economic games) can improve the level of cooperation 14 . Another study found that the introduction of integrative institutions activates altruism and improves cooperation among deeply divided ethnoreligious groups 15 . A series of studies found that an exposure to oxytocin through nasal intake improved the level of cooperation 16,17 .…”
mentioning
confidence: 99%